Dampak Peningkatan Bagi Hasil Pajak dan Belanja Sektor Riil Terhadap Penurunan Kemiskinan Pertanian di Indonesia - Lisna, Vera; Sinaga, Bonar M.; Sutomo, Slamet (Jurnal Agro Ekonomi, 2014)
EnglishFiscal decentralization policy in Indonesia, i.e. high composition of General Allocation Fund (DAU) on local financial structure and low tax revenue sharing successfully accelerates national economic growth but poverty reduction is slower and poor people proportion in the agricultural sector increases. Objective of this study is to analyze impacts of increased tax revenue sharing and local government expenditures in the real sector on regional economy and poverty that benefit agricultural poor people and reduce dependency on DAU. This study employs an econometric approach using a simultaneous equation system throughout 23 provinces during the period of 2005-2011 and a Two Stage Least Squares (2SLS) estimation method. An impact analysis is performed using policy simulations for the period of 2009-2011. Findings of this study are: (1) tax revenue sharing is significantly positive influenced by non-agricultural Gross Domestic Regional Product (GDRP) as a proxy of individual income taxes (VAT) as well as province area as a proxy of tax on land and building (PBB) and duty on the acquisition of land and building right (BPHTB), while DAU is significantly negative influenced by GDRP and significantly positive influenced by number of local civil servants; (2) changes in fiscal capacity is responded more by agricultural and infrastructure expenditures, while change in DAU is responded more by industrial and trade spending; (3) the poverty rate (headcount index) is negative significantly influenced by per capita expenditure and positive significantly influenced by the Gini Index of each sector; and (4) policy on increasing local financial income from tax revenue sharing allocated more for agricultural and industrial expenditures accelerates agricultural poverty reduction expected to reduce national poverty. IndonesianImplementasi desentralisasi fiskal dimana komposisi Dana Alokasi Umum (DAU) pada total pendapatan daerah relatif tinggi, sementara komposisi bagi hasil pajak rendah telah mempercepat laju pertumbuhan ekonomi nasional, tetapi laju penurunan kemiskinan melambat bahkan proporsi penduduk miskin pertanian meningkat. Penelitian ini bertujuan menganalisis dampak peningkatan bagi hasil pajak dan belanja sektor riil terhadap perekonomian dan kemiskinan sektoral daerah yang memihak penduduk miskin pertanian serta mengurangi ketergantungan keuangan daerah pada DAU. Analisis menggunakan pendekatan ekonometrik dengan membangun model sistem persamaan simultan dengan metode estimasi Two Stage Least Squares (2SLS) untuk data di 23 provinsi tahun 2005-2011, sementara analisis dampak dengan simulasi kebijakan periode historis tahun 2009-2011. Beberapa temuan penting yaitu: (1) penerimaan bagi hasil pajak secara signifikan positif dipengaruhi PDRB nonpertanian sebagai proksi pajak-pajak penghasilan (PPh) dan luas wilayah sebagai proksi Pajak Bumi dan Bangunan (PBB) dan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB), sedangkan penerimaan DAU secara signifikan negatif dipengaruhi PDRB dan secara signifikan positif dipengaruhi jumlah PNS daerah; (2) perubahan kapasitas fiskal direspon lebih besar oleh belanja pertanian dan infrastruktur, sedangkan perubahan DAU direspon lebih besar oleh belanja perindustrian dan perdagangan; (3) tingkat kemiskinan sektoral (headcount index) secara signifikan negatif dipengaruhi pengeluaran per kapita dan secara signifikan positif dipengaruhi Indeks Gini masing-masing sektor; dan (4) kebijakan peningkatan bagi hasil pajak yang dialokasikan lebih besar untuk belanja pertanian dan perindustrian berdampak menurunkan tingkat kemiskinan penduduk pertanian lebih besar sehingga dapat mempercepat laju penurunan kemiskinan nasional.